Pengaruh Kemudahan Penggunaan Dan Kualitas Sistem Byond BSI Terhadap Kepuasan Nasabah - Harahap, Annisa Oktavia; Rahmadani; Supaino; Zulhendry; Ermyna Seri (Jurnal Ekonomi Syariah Pelita Bangsa, 2025)
This study aims to analyze the effect of ease of use and system quality on customer satisfaction, with respondents being Muslim students of Politeknik Negeri Medan. The research employs a quantitative approach using survey techniques. Data were collected through a Likert-scale questionnaire distributed to 100 respondents and analyzed using multiple linear regression with the assistance of SPSS version 26. The results show that, partially, the ease of use variable does not have a significant effect on customer satisfaction. Conversely, system quality has a positive and significant effect on satisfaction. Simultaneously, ease of use and system quality also have a positive and significant influence on customer satisfaction. The coefficient of determination (R²) value of 0.500 indicates that 50% of the variation in customer satisfaction can be explained by the two independent variables. The conclusion of this study emphasizes the importance of system quality in enhancing customer satisfaction with Islamic digital banking applications. These findings align with the Technology Acceptance Model (TAM) approach and the principles of Maqashid Sharia.